MODEL PEMBELAJARAN PENDIDIKAN KARAKTER DENGAN PENDEKATAN MULTIKULTURAL DALAM PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI - A. Rosyid Al Atok; Suparlan Al Hakim; Sri Untari; Margono Margono (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: This research aims to develop a learning model character education with a multicultural approach used in Civic Education. The resulting learning model is poured in the form of modules and visualized in the form of instructional videos. Framework of a prototype model of learning by taking into account the competence of the subjects that must be owned by the students, faculty compe-tence in multicultural approach, the cultural background of students, and the characteristics of learning the nuances of multicultural material. Strategies that can be used, among others: strategies and learning activities are combined with the concept attainment strategy, the strategy value analy-sis, and strategies of social analysis. Drafting of the learning can be done through five main stages, namely content analysis, the analysis of cultural background, mapping materials, organizing materi-als, and then poured in Civic Education learning format. In the implementation of character education learning model with a multicultural approach can be done through the following phases: Exploration Studies, Presentations, Peer Group Analysis, Expert Opinion, and Reflections and Recommenda-tions.Keywords: character education, multicultural, and civic education